The Flipside of Comparative Payment Schemes - Thomas Buser; Anna Dreber (Tinbergen Institute, 2013)
Comparative payment schemes and tournament-style promotion mechanisms are ubiquitous in the work place. We test experimentally whether they have a negative impact on the willingness to cooperate. Participants first perform in a simple task and then participate in a public goods game. The payment scheme for the task varies across treatment groups. Compared to a piece-rate scheme, individuals in a winner-takes-all competition are significantly less cooperative in the public goods game. A lottery treatment, where the winner is decided by luck, has the same effect. In a competition treatment with feedback, winners cooperate as little as participants in the other treatments, whereas losers cooperate even less. All three treatments lead to substantial losses in the realised social surplus from the public good while having no significant impact on performance. The public go ods game is payoff-independent and is played with a separate set of others; we therefore estimate a psychological effect of comparative pay on the willingness to cooperate.
Keywords: D03; D23; J16; J33; 330; comparative pay; competition; cooperation; gender differences; incentive schemes